GreedyZero algorithms for conflict-free scheduling in low stage interconnection network - Moudi, Mehrnaz; Othman, Mohamed (Elsevier, 2015)
Low Stage Interconnection Networks are a class of Interconnection Networks. They have been generated from Multistage Interconnection Networks (MINs). Although the conflict in the optical switches, there is the considerable interest to use the optical technology in interconnection networks implementation. To avoid this problem, GreedyZero algorithms has been assigned to the Low Stage Interconnection Networks for improving the network performance by reducing the number of passes. The results marked nearly 50% reduction in the number of passes and proved improvement of scheduling in the Low Stage Interconnection Networks by GreedyZero algorithms.